Typical weekly physical periodization in French academy soccer teams: a survey - Douchet, Tom; Paizis, Christos; Carling, Christopher; Cometti, Carole; Babault, Nicolas (Biology of Sport, 2023)
In elite-level youth soccer players, weekly training periodization is of paramount importance to plan for short- and long-term physical development. The present study investigated current practices for physical periodization strategies in elite male French academies. An online survey was completed by elite French academies strength and conditioning coaches to determine the typical weekly periodization with particular reference to daily training in relation to match day (MD) in youth soccer players. The survey attempted to characterize the importance of physical development compared to match result, and practices used (expected difficulty and content) for each training session according to duration, exercises, and objective. The frequency rates of the responses were compared using two-tailed Chi-square tests with the significance level set at p < 0.05. Forty five questionnaires were analyzed. Respondents indicated that their training sessions focused mainly on physical development (95.6%) rather than match result. Active recovery (34.2%) and aerobicconditioning exercises (40.8%) were primarily conducted on MD+1 and MD+2 using passing circuits and aerobic technical drills. Physical development was mostly pursued during sessions on MD-4 (38.8%) and MD-3 (37.3%). The number of large-sided games was highest on MD-3 (58.1%). On MD-2 and MD-1, a decrease in the training load was highlighted, with speed (40.4%) and tapering sessions (52.4%) mostly implemented. Intensive use ofsmall-sided games (92.3%) and reactivity exercises was observed at MD-1 (100.0%). Our resultsrevealed discrepancies between the physical objectives set for each day and the content implemented, which could potentially be more physically demanding than expected.